2018
DOI: 10.1016/j.nlm.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the hypothesis that phasic dopamine constitutes a cached-value signal

Abstract: The phasic dopamine error signal is currently argued to be synonymous with the prediction error in Sutton and Barto (1987, 1998) model-free reinforcement learning algorithm (Schultz et al., 1997). This theory argues that phasic dopamine reflects a cached-value signal that endows reward-predictive cues with the scalar value inherent in reward. Such an interpretation does not envision a role for dopamine in more complex cognitive representations between events which underlie many forms of associative learning, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…In addition, identity PEs in the midbrain correlate with updates of outcome identity expectations in the orbitofrontal cortex (OFC) (Howard and Kahnt, 2018). This suggests a broader role for dopamine in associative learning, involving features beyond value (Gardner et al, 2018; Sharpe and Schoenbaum, 2018).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, identity PEs in the midbrain correlate with updates of outcome identity expectations in the orbitofrontal cortex (OFC) (Howard and Kahnt, 2018). This suggests a broader role for dopamine in associative learning, involving features beyond value (Gardner et al, 2018; Sharpe and Schoenbaum, 2018).…”
Section: Introductionmentioning
confidence: 98%
“…Seminal studies have shown that dopaminergic neurons in the midbrain display firing patterns consistent with these errors, which have been taken as a neural substrate of reward learning (Schultz et al, 1997; Schultz et al, 2017). Interestingly, unlike the original formulation of PEs as a teaching signal that is agnostic to the type of information that is encoded, dopaminergic PE responses have been conceptualized to exclusively respond to the difference between the value of expected and received outcomes (Glimcher, 2011; Sharpe and Schoenbaum, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…ACC neurons and ensembles also encode a regency-weighted history of past outcomes (Seo & Lee 2007;Bernacchia et al 2011;Hyman et al 2017) and it has been argued that these signals might produce the value representations that ultimately guide foraging decisions Wittmann et al 2016). The idea that action representations accrue value through an experience-dependent process is consistent with theories of reinforcement learning (RL) in mesolimbic pathways where value representations are thought to be continuously updated through a dopamine-dependent process (Stauffer et al 2014;Schultz 2015;Kolling & Akam 2017;Sharpe & Schoenbaum 2018).…”
Section: Introductionmentioning
confidence: 77%
“…Overall, our results show that transitions from phasic to ramping activity reflect widespread resource distribution, which allow rapid adaptation to potential changes in the stimulus value. Recent studies have found that the dopamine neurons are responsive to novel stimuli [60,61], changes to reward features [62,63], and stimuli that are potentially relevant to a given task [2][3][4][64][65][66].…”
Section: The Transition From Phasic To Ramping Patterns Upon Changes mentioning
confidence: 99%